Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00134-008-1333-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the soluble triggering receptor expressed on myeloid cells-1 in bacterial infection: a meta-analysis

Abstract: sTREM-1 represents a reliable biological marker of bacterial infection, but it may be not a sufficient biological marker for infection of the urinary tract as a result of its low sensitivity. Whether sTREM-1 guidance can reduce antibiotic use as well as the measurement of sTREM-1 in different types of infection will require additional prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 48 publications
0
55
2
2
Order By: Relevance
“…(25) Other studies also showed that sTREM is a sensitive marker for establishing the diagnosis of sepsis. (11,26) In the study that also tested the diagnostic value of sTREM-1 in patients with sepsis and sterile SIRS, concentrations of this biomarker were significantly higher in septic patients than in patients with sterile SIRS. (27) A meta-analysis, that included 11 studies and 1795 patients, found that sTREM had a sensitivity and specificity of 79% and 80% (respectively) in differentiation of sepsis from sterile SIRS.…”
Section: Resultsmentioning
confidence: 99%
“…(25) Other studies also showed that sTREM is a sensitive marker for establishing the diagnosis of sepsis. (11,26) In the study that also tested the diagnostic value of sTREM-1 in patients with sepsis and sterile SIRS, concentrations of this biomarker were significantly higher in septic patients than in patients with sterile SIRS. (27) A meta-analysis, that included 11 studies and 1795 patients, found that sTREM had a sensitivity and specificity of 79% and 80% (respectively) in differentiation of sepsis from sterile SIRS.…”
Section: Resultsmentioning
confidence: 99%
“…In Gibot et al 's study conducted to investigate the diagnostic values of both procalcitonin and sTREM-1, laboratory findings of both markers were higher in patients with sepsis (10). In another study investigating the diagnostic value of the sTREM-1 in patients with sepsis and NI-SIRS, sTREM-1 levels were significantly higher in patients with sepsis than in patients with NI-SIRS (17). In a metaanalysis of 13 studies, it was concluded that sTREM-1 levels could be considered a reliable biological marker in bacterial infections (18).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] When sTREM-1 of plasma is >60 μg/L in ICU sepsis patients, it is more accurate than any other clinical or laboratory indicators in predicting infection and sepsis with a sensitivity of 96% and a specificity of 89%. [15] A study found that sTREM-1 concentration was significantly lower at admission in non-survivors than in survivors.…”
Section: Discussionmentioning
confidence: 99%